The myosin-interacting protein SMYD1 is essential for sarcomere organization - Just, Steffen; Meder, Benjamin; Berger, Ina Maria; Etard, Christelle; Trano, Nicole; Patzel, Eva; Hassel, David; Marquart, Sabine; Dahme, Tillman; Heilmeier, Britta; Fishman, Mark C.; Katus, Hugo; et al. (Journal of cell science, 2011)
Assembly, maintenance and renewal of sarcomeres require highly organized and balanced folding, transport, modification and degradation of sarcomeric proteins. However, the molecules that mediate these processes are largely unknown. Here, we isolated the zebrafish mutant flatline (fla), which shows disturbed sarcomere assembly exclusively in heart and fast-twitch skeletal muscle. By positional cloning we identified a nonsense mutation within the SET- and MYND-domain-containing protein 1 gene (smyd1) to be responsible for the fla phenotype. We found SMYD1 expression to be restricted to the heart and fast-twitch skeletal muscle cells. Within these cell types, SMYD1 localizes to both the sarcomeric M-line, where it physically associates with myosin, and the nucleus, where it supposedly represses transcription through its SET and MYND domains. However, although we found transcript levels of thick filament chaperones, such as Hsp90a1 and UNC-45b, to be severely upregulated in fla, its histone methyltransferase activity - mainly responsible for the nuclear function of SMYD1 - is dispensable for sarcomerogenesis. Accordingly, sarcomere assembly in fla mutant embryos can be reconstituted by ectopically expressing histone methyltransferase-deficient SMYD1. By contrast, ectopic expression of myosin-binding-deficient SMYD1 does not rescue fla mutants, implicating an essential role for the SMYD1-myosin interaction in cardiac and fast-twitch skeletal muscle thick filament assembly.
Gesehen am 06.07.2022